2008
DOI: 10.1021/ol800596c
|View full text |Cite
|
Sign up to set email alerts
|

Mo−Au Combo Catalysis for Rapid 1,3-Rearrangement of Propargyl Alcohols into α,β-Unsaturated Carbonyl Compounds

Abstract: The combination of Mo and cationic Au catalysts dramatically accelerated the rearrangement of diverse propargyl alcohols, which includes a short reaction time, mild conditions, and high product yields. A practical application to the highly challenging primary propargyl alcohols and the N-alkynyl amides is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(70 citation statements)
references
References 22 publications
2
67
0
1
Order By: Relevance
“…Since the enone substructure of 27 is part of a 12‐membered ring and hence any cycloalkyne precursor necessarily strained, the macrocyclization by RCAM as well as the rearrangement chemistry are deemed fairly challenging. In fact, additional intelligence had suggested that an approach to dehydrocurvularin via a Meyer–Schuster rearrangement might be stereo‐unselective 50. Therefore we opted for the redox route shown in Scheme , which commenced with formylation of the commercial aryl bromide 28 followed by addition of propynylmagnesium bromide and protection of the resulting alcohol with a TBS group.…”
Section: Resultsmentioning
confidence: 99%
“…Since the enone substructure of 27 is part of a 12‐membered ring and hence any cycloalkyne precursor necessarily strained, the macrocyclization by RCAM as well as the rearrangement chemistry are deemed fairly challenging. In fact, additional intelligence had suggested that an approach to dehydrocurvularin via a Meyer–Schuster rearrangement might be stereo‐unselective 50. Therefore we opted for the redox route shown in Scheme , which commenced with formylation of the commercial aryl bromide 28 followed by addition of propynylmagnesium bromide and protection of the resulting alcohol with a TBS group.…”
Section: Resultsmentioning
confidence: 99%
“…1‐(Oct‐1‐yn‐1‐yl)cyclohexanol (3j): 2g Pale yellow oil. IR (film): $\tilde {\nu}$ = 3392, 2932, 2858, 1698, 1448, 1379, 1341, 1332, 1258, 1179, 1132, 1066, 1057, 964, 904 cm –1 .…”
Section: Methodsmentioning
confidence: 99%
“…In 2008, Akai's group [26] described a very efficient Meyer-Schuster rearrangement by the combined use of MoO 2 (acac) 2 [27] reported another practical synthesis of linear α-iodo/ bromo-β-unsaturated aldehydes/ketones directly from propargylic alcohols (Scheme 18). In this reaction, two metals complexes, MoO 2 (acac) 2 and PPh 3 AuNTf 2 catalyzed this reaction collaboratively.…”
Section: Gold/lewis Acid Bimetallic Catalysismentioning
confidence: 99%